(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
We present two new leads with Iberic inscriptions, found in the Museu d’Arqueologia de Catalunya-Barcelona and the Museu Torre Balldovina; they are supposed to come from the Puig Castellar Iberian oppidum (Santa Coloma de Gramenet).